2020
DOI: 10.1021/acs.langmuir.0c00643
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Sophorolipid Biosurfactant and SDS Increases the Efficiency of P. aeruginosa Biofilm Disruption

Abstract: Biofilms are communities of bacteria encased in selfsecreted extracellular polymeric substances (EPS) that adhere stubbornly to submerged surfaces. Once established, these communities can cause serious chronic illnesses in medical settings, while they can promote corrosion and biofouling in industrial settings. Due to the difficulty of their removal, strongly oxidizing chemicals and detergents can be used to degrade and remove biofilms by killing the cells and degrading the matrix; however, the choice of compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 66 publications
(129 reference statements)
2
36
0
Order By: Relevance
“…L. rhamnosusderived biosurfactants cause cell lysis by disrupting the membrane structure, thus can be used as an anti-biofilm agent for multispecies biofilms on silicone devices, i.e., voice prostheses in case of laryngectomy (Tan et al, 2017). The anti-biofilm activity of biosurfactants can augment extensively in combination with caprylic acid that inhibits biofilm formation of P. aeruginosa, E. coli, and B. subtilis (Diaz De Rienzo et al, 2016); amphotericin B (AmB) or fluconazole synergistically acts against biofilm formation and preformed biofilm of C. albicans (Haque et al, 2016); and surfactants such as SDS led to the destruction of P. aeruginosa PAO1 biofilms (Nguyen et al, 2020).…”
Section: Biosurfactantsmentioning
confidence: 99%
“…L. rhamnosusderived biosurfactants cause cell lysis by disrupting the membrane structure, thus can be used as an anti-biofilm agent for multispecies biofilms on silicone devices, i.e., voice prostheses in case of laryngectomy (Tan et al, 2017). The anti-biofilm activity of biosurfactants can augment extensively in combination with caprylic acid that inhibits biofilm formation of P. aeruginosa, E. coli, and B. subtilis (Diaz De Rienzo et al, 2016); amphotericin B (AmB) or fluconazole synergistically acts against biofilm formation and preformed biofilm of C. albicans (Haque et al, 2016); and surfactants such as SDS led to the destruction of P. aeruginosa PAO1 biofilms (Nguyen et al, 2020).…”
Section: Biosurfactantsmentioning
confidence: 99%
“…In recent decades, there have been a significant number of reports on the bioactivities of glycolipids. However, many of these reports either utilized poorly characterized, impure preparations or only a single class of glycolipids whose proportion and percentage purity may not have been reported [9,26,[44][45][46][47][48][49][50][51]. Therefore, in this study, to investigate the effects of microbial glycolipids with different chemical structures on skin cells, the congeners present in the glycolipid preparations utilized were first rigorously characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm volume has also been reduced after a single surfactant exposure event, with decreases of 26.5-98.1% occurring between 22-48 hours after exposure (Mireles II et al ., 2001; Quinn et al ., 2013). However, previous work on surfactant effects have also shown that biofilms demonstrate resistance and can recover full respiratory activity 12 hours after the initial exposure (Simoes et al ., 2008) and biomass 5 hours after initial exposure (Nguyen et al ., 2020). Therefore, the length of our experiment of 32 days may have been long enough where GPP, CR, and AFDM could be stable over time, despite the permanent exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work on surfactant effects have also shown that biofilms demonstrate resistance and can recover full respiratory activity 12 hours after the initial exposure (Simoes et al . 2008) and biomass 5 hours after initial exposure (Nguyen et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation